Effect of cavity disinfection protocols on microtensile bond strength of universal adhesive to dentin = Efecto de los protocolos de desinfección de cavidades en la fuerza de adhesión microtensil del adhesivo universal a la dentina - Bilgili Can, Dilber; Dundar, Ayse; Barutcugil, Çagatay (2022)
The purpose of this study was to compare the effect of different disinfection protocols of dentin on bond strength of an MDP-containing universal adhesive. Twelve extracted mandibular third molars were separated horizontally at the mid-coronal of crown to get smooth and sound dentin surfaces using low-speed diamond saw. The teeth were randomly fallen into four groups: chlorhexidine (CHX), ozone, Er,Cr:YSGG laser irradiation (LASER) and no treatment (control). After cavity disinfection application, a universal adhesive (G-Premio Bond) was applied to the surface of dentin according to self-etch mode as instructed by the manufacturer. After incremental built-up of composite resin (Charisma Smart), the specimens were immersed in distilled water at 37°C for 24h. Dentin/composite beams with 1 mm² cross sectional area were produced and micro-tensile bond strength (μTBS) was applied on these beams (n=20). Failure mods were determined under a stereomicroscope at ×40. The resin penetration of samples stained with Rhodamine B fluorochrome dye was examined with a confocal laser scanning microscope. Statistical analysis was performed with SPSS-22. Test results were analyzed using One-way Anova and Tukey HSD Post-Hoc tests (p<0.05). The μTBS value of control (35.13±6.20) was the highest statistically among the groups (p<0.05). The lowest μTBS were obtained by LASER (19.25±4.66) and CHX (23.07±7.01). There was no significant difference between CHX and LASER, and between CHX and ozone (p>0.5). All applications of cavity disinfection procedures decreased the μTBS of the resin-dentin interface.
El propósito de este estudio fue comparar el efecto de diferentes protocolos de desinfección de la dentina sobre la fuerza de unión de un adhesivo universal que contiene MDP. Doce terceros molares mandibulares extraídos se quebraron horizontalmente en la mitad de la corona para obtener superficies de dentina lisas y sólidas utilizando una sierra de diamante de baja velocidad. Los dientes se dividieron aleatoriamente en cuatro grupos: clorhexidina (CHX), ozono, irradiación con láser Er,Cr:YSGG (LASER) y ningún tratamiento (control). Después de la aplicación de la desinfección de la cavidad, se aplicó un adhesivo universal (G-Premio Bond) a la superficie de la dentina según el modo de autograbado indicado por el fabricante. Después de la obturación con resina compuesta (Charisma Smart), las muestras se sumergieron en agua destilada a 37°C durante 24h. Se produjeron porciones de dentina/resina con un área de sección transversal de 1 mm² y se aplicó una fuerza de adhesión microtensile (μTBS) (n=20). Los modos de falla se determinaron bajo un microscopio estereoscópico a ×40. La penetración de la resina de las muestras teñidas con colorante fluorocromo rodamina B se examinó con un microscopio de barrido láser confocal. El análisis estadístico se realizó con SPSS-22. Los resultados de las pruebas se analizaron utilizando las pruebas post-hoc Anova unidireccional y Tukey HSD (p<0,05). El valor de μTBS del control (35,13±6,20) fue el más alto estadísticamente entre los grupos (p<0,05). Los μTBS más bajos los obtuvieron LASER (19,25±4,66) y CHX (23,07±7,01). No hubo diferencia significativa entre CHX y LASER, y entre CHX y ozono (p>0.5). Todas las aplicaciones de procedimientos de desinfección de cavidades redujeron el μTBS de la interfaz resina-dentina.
En revista Odóvtos, vol. 24, no. 3 (septiembre-diciembre 2022)
Descripción basada en el contenido visto el 05 de diciembre, 2024
También disponible en formato HTML y EPUB